The effect of minocycline on the masticatory movements following the inferior alveolar nerve transection in freely moving rats - Mostafeezur Rahman; Zakir Hossain; Yamada Yoshiaki; Yamamura Kensuke; Iwata Koichi; Sessle Barry J; Kitagawa Junichi (SAGE Publishing, 2012)
Abstract Background To determine the effects of inferior alveolar nerve transection (IAN-X) on masticatory movements in freely moving rats and to test if microglial cells in the trigeminal principal sensory nucleus (prV) or motor nucleus (motV) may be involved in modulation of mastication, the effects of microglial cell inhibitor minocycline (MC) on masticatory jaw movements, microglia (Iba1) immunohistochemistry and the masticatory jaw movements and related masticatory muscle EMG activities were studied in IAN-X rats. Results The number of Iba1-immunoreactive (IR) cells both in prV and motV was significantly larger in IAN-X rats compared with sham rats on day 3 after IAN-X. The intraperitoneal (i.p.) administration of MC caused a significant reduction of the number of Iba1-IR cells both in prV and motV that was evident on day 14 after IAN-X. Furthermore, a significant reduction of the number of Iba1-IR cells could be observed in motV but not in prV after microinjection (m.i.) of MC into the motV of IAN-X rats. The rats also exhibited a significant decrease in the head-withdrawal threshold on the side ipsilateral to the IAN-X compared to the threshold before IAN-X and it lasted to day 14. In addition, IAN-X markedly affected the ability to rat to carry out mastication. The number of complete masticatory sequences was significantly decreased. Furthermore, the total masticatory sequence time and food preparatory (PP) period duration was significantly elongated in compared to sham rats. Although IAN-X significantly affected the total number of chewing cycles within the RC period of a masticatory sequence, it had no effect on the duration of the chewing cycles. On the other hand, systemic administration of MC (both i.p. and m.i.) in IAN-X rats significantly improved decreased head-withdrawal threshold and the impaired masticatory jaw movements. Conclusions The present findings reveal that the strong modulation of masticatory jaw movements occurs following microglial cell activation after IAN-X, and the modulation recovers after inhibition of the microglial cell activation by MC, suggesting that microglial cell activation in the motV as well as in the prV has a pivotal role in modulating mastication following trigeminal nerve injury associated with orofacial neuropathic pain.